Minimize potential liabilities in collegiate sports medicine departments. Issue 8 (17th November 2014) - Neal, Timothy; Quandt, Eric; Thornton, James; Anderson, Jeffrey
Abstract : When collegiate sports medicine staff, other athletics department staff and institutions fail to properly address student‐athlete safety and welfare issues, you can bank on facing potential liability.